Doxorubicin-loaded micelles of amphiphilic diblock copolymer with pendant dendron improve antitumor efficacy: In vitro and in vivo studies - Voon, Siew Hui; Kue, Chin Siang; Imae, Toyoko; Saw, Wen Shang; Lee, Hong Boon; Kiew, Lik Voon; Chung, Lip Yong; Yusa, Shin-ichi (Elsevier, 2017)
Previously reported amphiphilic diblock copolymer with pendant dendron moieties (P 71 D 3 ) has been further evaluated in tumor-bearing mice as a potential drug carrier. This P 71 D 3 -based micelle of an average diameter of 100 nm was found to be biocompatible, non-toxic and physically stable in colloidal system up to 15 days. It enhanced the in vitro potency of doxorubicin (DOX) in 4T1 breast tumor cells by increasing its uptake, by 3-fold, compared to free DOX. In 4T1 tumor-bearing mice, the tumor growth rate of P 71 D 3 /DOX (2 mg/kg DOX equivalent) treated group was significantly delayed and their tumor volume was significantly reduced by 1.5-fold compared to those treated with free DOX. The biodistribution studies indicated that P 71 D 3 /DOX enhanced accumulation of DOX in tumor by 5- and 2-fold higher than free DOX treated mice at 15 min and 1 h post-administration, respectively. These results suggest that P 71 D 3 micelle is a promising nanocarrier for chemotherapeutic agents.